Characterization of wastewater from a small-scale gold mine located in Itogon, Benguet using physico-chemical parameters before and after coco-peat filtration - Beltran, Romeo F. Jr
This study is about the characterization of wastewater samples from a small-scale gold mine in Itogon Benguet before and after Filtration with the use of electric measuring device for water quality determination. This study combines sedimentation and filtration processes as its theoretical framework for treatment. In connection to sedimentation process, Settling column experiments were conducted to generate plots of isoconcentration lines that will help determine the detention time of the wastewater as well as its overflow rate value to come up with a design of an ideal settling basin. The use of a coco-peat column was done to serve as the filter for the treatment process. Color removal was done until effluent samples from washing the filter obtained a 150 pcu mark before filtration of settled wastewater to ensure that the color produced by the coco peat would not affect the color of the filtered wastewater. Physico-chemical parameters such as pH, temperature, Electric Conductivity, Oxygen Reduction Potential, Turbidity, Total Dissolved Solids, and Total Suspended Solids were used as parameters for the water quality analysis. Finally, this study was able to design an efficient sedimentation tank based on calculated detention time and overflow rate of wastewater as well as estimate a projected cost for the constrllction of an onsite wastewater treatment plant similar to this study.